Residual salt separation technique using centrifugal force for pyroprocessing - Sung-Wook Kim; Jong Kwang Lee; Dongseok Ryu; Min Ku Jeon; Sun-Seok Hong; Dong Hyun Heo; Eun-Young Choi (Nuclear Engineering and Technology, 2018)
Pyroprocessing uses various molten salts during electrochemical unit processes. Reaction products after the electrochemical processes must contain a significant amount of residual salts to be separated. Vacuum distillation is a common method to separate the residual salts; however, its high operation temperature may cause side reactions. In this study, a simple rotation technique using centrifugal force was suggested to separate the residual salts from the reaction products at relatively low temperature compared to the distillation technique. When a reaction product container with porous wall rotates inside a vessel heated above the melting point of the residual salt, the residual salt in the liquid phase is separated through centrifugal force. It was shown that the LiNO3-Al2O3 mixture can be separated by this technique to leave solid Al2O3 inside the container, with a separation efficiency of 99.4%. Keywords: Pyroprocessing, Molten salt, Salt separation, Liquid-solid separation, Centrifugal force